2011
DOI: 10.1007/s00223-011-9553-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of In Vivo Bone Dynamics in a Mouse Tail Model of Postmenopausal Osteoporosis

Abstract: Recently, it has been shown that transient bone biology can be observed in vivo using time-lapse microcomputed tomography (lCT) in the mouse tail bone. Nevertheless, in order for the mouse tail bone to be a model for human disease, the hallmarks of any disease must be mimicked. The aim of this study was to investigate whether postmenopausal osteoporosis could be modeled in caudal vertebrae of C57Bl/6 mice, considering static and dynamic bone morphometry as well as mechanical properties, and to describe tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Even in rats with lower rates of bone remodeling, the level of noise quantified in the current study remains significantly lower than previously measured differences in remodeling due to osteoporosis or drug treatment 1, 12 . Combined with previous studies by other groups 3, 16, 18, 21, 23 , this indicates that the in vivo dynamic bone histomorphometry technique has adequate precision to detect physiologically relevant changes in bone remodeling. In vivo dynamic bone histomorphometry has many strengths, including its ability to provide noninvasive, longitudinal measures.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Even in rats with lower rates of bone remodeling, the level of noise quantified in the current study remains significantly lower than previously measured differences in remodeling due to osteoporosis or drug treatment 1, 12 . Combined with previous studies by other groups 3, 16, 18, 21, 23 , this indicates that the in vivo dynamic bone histomorphometry technique has adequate precision to detect physiologically relevant changes in bone remodeling. In vivo dynamic bone histomorphometry has many strengths, including its ability to provide noninvasive, longitudinal measures.…”
Section: Discussionsupporting
confidence: 64%
“…In addition to tracking changes in the trabecular microstructure, several recent studies have developed in vivo dynamic bone histomorphometry techniques that utilize registered μCT images to identify regions of bone formation and resorption, allowing for longitudinal assessment of bone remodeling and structural changes in the caudal vertebra 16, 21, 23 and at the proximal tibia 3, 12 . In these studies, animals are scanned at multiple time-points, and the resulting μCT images are registered, thresholded, and subtracted to identify, on a voxel-by-voxel basis, locations where bone has formed or resorbed 3, 12, 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in female rats demonstrated significant alterations in bone morphology and muscle mass as early as two and four weeks, respectively, following ovariectomy 6, 13 .…”
Section: Methodsmentioning
confidence: 94%
“…Resorption is identified as the bone areas only present in the earlier images, while bone formation is identified as the bone areas only present in the later scans. This technique provides accurate quantification of bone remodeling in mouse caudal vertebrae in models of post-menopausal osteoporosis [29] and mechanical loading [28, 30, 31]. …”
Section: Introductionmentioning
confidence: 99%